PENGARUH SELF-CONFIDENCE PADA MATA PELAJARAN IPAS TERHADAP LITERASI SAINS DAN SIKAP ILMIAH MURID SEKOLAH DASAR - Fitriyadi Ningsih, Ajeng; Yuliyanti, Novi; Toharudin, Moh. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low student self-confidence in science learning is a problem at SD Negeri Songgom 05. Observation results show that only 20.8% of students dare to ask and answer questions voluntarily, while the other 79.2% tend to be passive. This study aims to analyze the effect of self-confidence on scientific literacy and scientific attitudes of fifth-grade students in the water cycle science subject through the implementation of outdoor learning models. This study uses a quantitative approach with a pretest-posttest control group design. The study population was fifth-grade students of SD Negeri Songgom 05 and SD Negeri Songgom 08. A sample of 50 students was determined using a saturated sampling technique, consisting of 25 students in the experimental class and 25 students in the control class. Data collection instruments were multiple-choice tests for scientific literacy and structured observation sheets for scientific attitudes. Data analysis used the Mann-Whitney U test, because the data did not have the same variance. The results showed that the Asymp. Sig. (2-tailed) value was 0.000 (<0.05) for scientific literacy, so Ha1 was accepted. Descriptive analysis showed that 76% of experimental class students achieved a very high level of scientific attitude (77%-100%) and 24% achieved a high level (51%-75%). The conclusion of this study is that self-confidence has a significant influence on scientific literacy and scientific attitudes of fifth grade students of Songgom 05 Elementary School on the water cycle material through outdoor learning models.